2012
DOI: 10.1016/j.ydbio.2012.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Early B-cell factors 2 and 3 (EBF2/3) regulate early migration of Cajal–Retzius cells from the cortical hem

Abstract: Cajal–Retzius (CR) cells play a crucial role in the formation of the cerebral cortex, yet the molecules that control their development are largely unknown. Here, we show that Ebf transcription factors are expressed in forebrain signalling centres—the septum, cortical hem and the pallial–subpallial boundary—known to generate CR cells. We identified Ebf2, through fate mapping studies, as a novel marker for cortical hem- and septum-derived CR cells. Loss of Ebf2 in vivo causes a transient decrease in CR cell numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 59 publications
(58 reference statements)
5
58
0
2
Order By: Relevance
“…In Arx (GCG)7 mice, ectopic Ebf3 expression in developing interneurons disrupted their migration, whereas Lmo1 and Shox2 remained repressed (42). Normally, Ebf1/2/3 genes appear to control embryonic migration of Cajal-Retzius cells (57). Lgi1 is a secreted protein expressed by central nervous system neurons that participates in synapse organization and neuronal growth (58, 59), and loss-of-function mutations are associated with temporal lobe epilepsy in human patients (60).…”
Section: Discussionmentioning
confidence: 99%
“…In Arx (GCG)7 mice, ectopic Ebf3 expression in developing interneurons disrupted their migration, whereas Lmo1 and Shox2 remained repressed (42). Normally, Ebf1/2/3 genes appear to control embryonic migration of Cajal-Retzius cells (57). Lgi1 is a secreted protein expressed by central nervous system neurons that participates in synapse organization and neuronal growth (58, 59), and loss-of-function mutations are associated with temporal lobe epilepsy in human patients (60).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports that Foxg1 can act as a transcriptional repressor (Yao et al, 2001), we observed an increased representation of TFs among the down-regulated genes (Figure 4) and showed that Foxg1 binds to these down-regulated genes in vivo (Figure 5). Interestingly, these TFs might not only be selectively expressed, but may also be required for CR cell development (Chiara et al, 2012; Inoue et al, 2008). These results indicate that the transition from early CR cell to the projection neuron production program involves the rapid repression of multiple TFs (≥20 hr), followed by delayed induction of up-regulated TFs (≥30 hr).…”
Section: Discussionmentioning
confidence: 99%
“…A transactivation domain (TAD) at the C terminus mediates activation of Ebf target genes 13,14 . As all four proteins share over 90% sequence homology within these domains, except for the TAD, all Ebf proteins bind to the same DNA sequence and can act redundantly [15][16][17] .…”
mentioning
confidence: 99%
“…Originally identified in neuronal cells 18,19 , Ebf3 is important for cell migration in the developing cortex 17 and in the projection of olfactory neurons to the olfactory bulb 16 . In Xenopus the homologue Xebf3 acts as a regulator of neuronal differentiation downstream of XNeuroD 20 .…”
mentioning
confidence: 99%